Platelet-Rich Gel Supernatants Stimulate the Release of Anti-Inflammatory Proteins on Culture Media of Normal Equine Synovial Membrane Explants - Diana L. Ríos; Catalina López; Jorge U. Carmona (Veterinary Medicine International)
The aims were as follows: (1) to evaluate the effects at 48 and 96 h of two concentrations (25 and 50%) of leukocyte and platelet-rich gel (L-PRG) and pure PRG (P-PRG) supernatants on the production/degradation in normal equine synovial membrane explants (SME) of platelet derived growth factor isoform BB, transforming growth factor beta-1, tumor necrosis factor alpha, interleukin (IL-) 4 (IL-4), IL-1 receptor antagonist (IL-1ra), and hyaluronan (HA) synthesis and (2) to correlate these molecules with their respective PRG supernatant treatments. SME from 6 horses were cultured for 96 h with L-PRG and P-PRG supernatants at 25 and 50% concentrations, respectively. SME culture media were changed each 48 h and used for determination by ELISA of the molecules, which were also determined in synovial fluid. 25% L-PRG supernatant produced a sustained release over time of IL-1ra and a gradual release of HA, whereas 50% L-PRG supernatant produced a sustained increase over time of IL-4 and HA. 50% P-PRG supernatant produced an increased and sustained production of IL-1ra and IL-4. The cellular composition and the articular concentration (volume) of a platelet-rich plasma preparation could affect the anti-inflammatory and anabolic joint responses in horses with osteoarthritis.